KORELASI LEVEL AKTIVITAS FISIK DENGAN KUALITAS TIDUR DAN TINGKAT STRES PADA MAHASISWA - Haniffah Mardiah, - (2022)
The purpose of this study was to determine the relationship between physical activity levels and sleep quality and stress levels in college students. This study used a correlational design, involving 41 (33 female and 8 male) third, fifth, and seventh semester students of the Universitas Pendidikan Indonesia (UPI) as samples. The study was conducted in two stages, namely (1) data collection on physical activity levels using the accelerometer actigraph WGT3X-BT and (2) data collection on sleep quality using the Pittsburgh Sleep Quality Index (PSQI) and stress levels using the Depression Anxiety Stress Scale 21 (DASS-21). Hypothesis testing uses multivariate pearson correlation to determine the relationship between variables. The results of the data analysis showed that there was no significant relationship between the level of physical activity and sleep quality and stress levels in college students. This can be seen from the statistical value (p = 0.15 > 0.05) between the level of physical activity and sleep quality, and (p = 0.41 > 0.05) between the level of physical activity and the level of stress. The findings of these researchers indicate that the level of physical activity is not closely related to sleep quality and stress levels in college students. However, a more in-depth study related to this problem needs to be done.